Rynkowy model wczesnej edukacji a stanowisko profesjonalistów – perspektywa globalna - Eugenia Potulicka (Problemy Wczesnej Edukacji)
The text presents an analysis of global sources of the increasing expansion of the market model in the field of early childhood education, understood as all institutional types of pre-schooling education. The importance of this stage of education for the child’s development – especially in disadvantaged groups – and its subsequent functioning at school does not seem to be questionable in the light of the research results cited. Nonetheless, the possibility of every child’s access to good, public, and free early education is far from satisfactory. Consideration of this issue from the economic, educational, and political perspectives reveals a number of tensions and problems, conditioned locally and globally. One of the key issues is the opposition between the market model of early childhood education and aspirations to implement democratic solutions supporting these wide learning objectives for children. However, the economic crisis makes education in the field of early childhood education require public and private partnership, implemented in the context of specific government regulations.